Literature Study: Mountain Scrubbing as Landslide and Flash Flood Disaster Mitigation Based on Local Wisdom in Java - Khoirotul Ummah; Nur Aisyah; Vina Rachma Yunita; Wahyu Bunga Anjani; Nasywa Nabilah Azzahra (Journal of Community Development and Disaster Management, 2025)
Indonesia is one of the countries with the highest disaster vulnerability in the world, particularly to flash floods and landslides due to its geographical conditions dominated by hilly areas, high rainfall, and land use changes. In this context, local wisdom plays a crucial role as an adaptive and sustainable community-based mitigation strategy. One form of local wisdom that is often used is Nyabuk Gunung, a technique for managing sloping land by following contour lines to resemble a "belt" encircling the mountain. By breaking water flow, increasing infiltration, slowing surface runoff, and stabilizing soil structure with the support of deeply rooted vegetation, this system has been proven to reduce the risk of erosion, landslides, and peak discharge of flash floods. This literature study aims to examine the application of Nyabuk Gunung in various mountainous areas of Java and comparing other regions such as Bali, Sunda, and even indigenous communities such as the Baduy and Ciptagelar. The results of the study indicate that this practice not only serves to maintain environmental sustainability but also is an integral part of the community's agrarian culture. Although implementation varies across regions, ranging from full terracing to elongated planting patterns, the principles of soil and water conservation remain consistent. The preservation and revitalization of Nyabuk Gunung has become an important urgency amidst modernization to strengthen hydrometeorological disaster resilience in a sustainable manner.